Kitab Al-Sirat Al-Mustaqim Oleh Shaykh Nur Al-Din Al-Raniri: Satu Sorotan - Jamalluddin, Hashim; Abdul Karim, Ali (2008)
Syeikh Nur al-Din al-Raniri, known as al-Raniri was a prolific author on various disciplines of Islamic studies such as teology, fiqh and governance. Among of his out standing works are Hujjah al-Siddiq Li Daf‘ al-Zindiq, al-Tibyan fi Ma‘rifah al-Adyan, Hall al-Zill, al-Sirat al-Mustaqim and Bustan al-Salatin. As far as the al-Sirat al-Mustaqim is concerned, it is considered the oldest and earliest work on fiqh by Muslim scholars of Southeast Asia. This article endeavours to elucidate the importance of this work by revealing works, literatures and sources pertaining to al-Sirat al-Mustaqim.